ASPIRASI MASYARAKAT TERHADAP PENDIDIKAN JARAK JAUH DI KAMPUNG RAMAH ANAK SURYOWIJAYAN RW 01 YOGYAKARTA - Wicaksono, Yoga Asadi Unggul (Spektrum Analisis Kebijakan Pendidikan, 2022)
This research aims to describe people's aspirations for distance education (PJJ) during the pandemic, factors that affect aspiration, and the implementation of distance education in Kampung Ramah Anak (KRA) Suryowijayan RW 01. Research uses a qualitative approach. The research subjects consist of students, parents, and community leaders. Data is collected through interviews, observations, and documentation. Data analysis techniques with interactive analysis consisting of data condensation, data presentation, and conclusion withdrawal. The validity of the data is tested by triangulation of sources and techniques. The aspirations of the community show that the implementation of PJJ in KRA has not been effective. The aspirations of the community consist of the need for coordination of all components ofÂ education, schoolÂ innovation, improved teacher professionalism, KRA optimization, and increased parental responsibility are discussed in this article. These aspirations are formed by being influenced by personal factors and environmental factors.Keywords: Community Aspiration, Distance Learning, Child-Friendly VillageÂ